Initial Studies of Validity of the Sensory Processing 3-Dimensions Scale. (2nd January 2019) - Mulligan, Shelley; Schoen, Sarah; Miller, Lucy; Valdez,, Andrea; Wiggins, Aryanna; Hartford, Brianna; Rixon, Amy
ABSTRACT: Aims : This study examined the validity of a new measure of sensory processing for children, the Sensory Processing 3-Dimensions Scale (SP-3D). The SP-3D is a performance-based measure for children ages three to thirteen years, designed to assess sensory processing abilities, and identify the three patterns of sensory processing disorder (SPD) and related subtypes, including sensory modulation, sensory discrimination, and sensory-based motor disorders. Methods : Age trends were explored using descriptive statistics and graphing techniques with a sample of children with and without SPD. SP-3D scores were correlated with scores from the Sensory Processing Measure (SPM) to examine criterion-related validity. Discriminant validity was assessed by comparing SP-3D scores from children with and without SPD. Results : Age trends of SP-3D scores supported sensory discrimination, praxis and postural functions as developmental constructs. Several mild to moderate correlations were found between the scores of the SP-3D and the SPM, indicating that the tools are measuring similar constructs, and supporting the SP-3D as a measure of sensory processing. Modulation and Motor Behavior Scores from the SP-3D discriminated typically developing children from those with SPD, while results from subtests measuring sensory discrimination, postural and praxis were mixed regarding capacity for discrimination suggesting revision to several items. Conclusion : The study provides preliminary evidence of the SP-3D as a valid measure of sensory processing abilities and dysfunction. Further research regarding the reliability and validity of the SP-3D are needed.